Biomimetic growth of hydroxyapatite on phosphorylated electrospun cellulose nanofibers - Li, Kaina; Wang, Jiangnan; Liu, Xinqing; Xiong, Xiaopeng; Liu, Haiqing (Carbohydrate polymers, 2012)
► Electrospun cellulose nanofiber/hydroxyapatite composites were synthesized. ► Phosphorylated cellulose nanofibers were highly bioactive in inducing the HAp growth. ► The composites are porous materials with micro-, meso-pores and pores in micrometer. ► The composites can be potentially useful in the field of bone tissue engineering. In biomimicking the formation of collagen fiber/hydroxyapatite (HAp) in natural bone, electrospun cellulose nanofiber (CelluNF)/HAp composites were synthesized in simulated body fluid (SBF). Their morphology and structure were characterized by SEM, TEM, XRD and XPS. CelluNFs showed low bioactivity in inducing the growth of HAp. In order to improve this ability, CelluNFs were slightly phosphorylated with a degree of substitution of phosphate group of 0.28. The modified CelluNFs were highly effective in guiding the HAp growth along the fibers. The HAp crystal size in the composites was ca. 24nm, and the lattice spacing of (211) plane was 2.83Å. It was found that the HAps in the composites were calcium deficient. The CelluNF/HAp composites are highly porous materials with micro-, meso-, and macro-pores. A mechanism for the HAp growth on CelluNFs was presented. Such CelluNF/HAp composites can be potentially useful in the field of bone tissue engineering.